The Application of Knowledge Management in The United States Agency for International Development ( USAID ) - Hendrawan, Muhammad Rosyihan (Record and Library Journal, 2016)
Knowledge management (KM) has a strategic and vital position to the existence of an organization. USAID as an global organization which has a working area of promoting transnational cultural knowledge in existence. USAID has been Able to run continuously through the KM division specifically created to carry out a series of policies that have been determined by the USAID. As a worldwide organization, USAID has been very worth implementing its own strategic system in an effort to reach every knowledge management of the latest and dynamic information so that it can be an organizations intellectual assets for sustainability in the era of globalization. Expected with the implementation of KM system will be Able to improve the performance of the organization so that it has a competitive advantage in the face of global competition.